Chronic Suppurative Osteomyelitis of Mandible: A Case Report - Mehra, Hemant (Thieme Medical Publishers, 2013)
Osteomyelitis is an inflammatory disease of the bone that usually begins as an infection of the medullary cavity, rapidly involves the haversian system, and quickly extends to the periosteum of the area. It develops in the jaws after a chronic odontogenic infection or for a variety of other reasons such as trauma, inadequate treatment of fracture, or irradiation to the mandible. When antimicrobial agents or drainage prove unsuccessful, acute osteomyelitis may become chronic. Conventional radiography, culture, bone biopsy, radioisotope bone scan, laser Doppler flowmetry, computed tomography, and magnetic resonance imaging are used for its diagnosis. We present a case of chronic suppurative osteomyelitis associated with a draining extraoral sinus, which was successfully treated with surgical debridement and stabilization with a 10-hole reconstruction plate and bicortical screws using AO principles.